11. Bursa Body Weight Ratio in ALPU Chickens - Vinky Claudya Fransiska; Erina Erina; Mahdi Abrar; M Aman Yaman; Ummu Balqis; M. Jalaluddin (Jurnal Medika Veterinaria, 2020)
This study was aimed to determine ratio of bursa body weight in ALPU chickens. The samples used were 72 ALPU chickens consisting of 36 males and 36 females aged 1-18 weeks. This study was observed in every week by weighing the weight of ALPU chickens as much as 2 males and 2 females, then chickens slaughtered. After that, Fabricius's bursa on each chicken was separated from the chicken body part and weighed using a digital balance sheet. The results of this study showed that the maximal ratio in male ALPU chickens was 0.0032 at the age 2 weeks, while the maximal ratio in female ALPU chickens was 0.0036 at the age 4 weeks. From the results of the analysis using t-test was concluded that bursa body weight ratio in male and female ALPU chickens during starter to grower group was significantly different (p0.05). The grower to finisher group was not significantly different (p0.05).